Demo-scale production of protein-rich fungal biomass from potato protein liquor for use as innovative food and feed products. (June 2022) - Sar, Taner; Larsson, Karin; Fristedt, Rikard; Undeland, Ingrid; Taherzadeh, Mohammad J.
Abstract: Innovative food and feed products have recently attracted the attention of both producers and consumers. Filamentous fungi are important biomass producers with their high protein contents. In this study, fungal biomass production from edible potato protein liquor (PPL), generated during starch production processes, was investigated through different fungal strains ( Rhizopus oryzae, R. oligosporus, R. delemar, Aspergillus oryzae and Neurospora intermedia ). The effects of PPL concentration, incubation time, initial pH, and cultivation conditions (in shake flaks and different scale reactors) were examined to determine the amount of biomass and its crude protein level. It was determined that the fungal biomass produced by R. delemar in industrial scale contained 53% crude protein. For this strain, the amino acid and fatty acid profiles as well as metals (iron, manganese, copper, and zinc) of the produced biomass were also investigated to assess possible use as a food or feed source. The R. delemar fungal biomass can be a promising raw material for feed and food production, for example, considering its protein and fatty acid profiles with 41% essential amino acids and 33% polyunsaturated fatty acids. Graphical abstract: Image 1 Highlights: Fungal biomass containing 53% crude protein was produced in a demo-scale reactor. Initial pH of the potato protein liquor (PPL) affected the amount of biomass and its protein content. Produced fungal biomass from PPL contained significant amounts of some essential metals. The percentages of SFAs, MUFAs and PUFAs in biomass were found at similar levels. Essential amino acids in fungal biomass contributed to 41% of the total amino acids.